2019
DOI: 10.1088/1742-6596/1299/1/012130
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of phase equilibria in multicomponent water-salt systems by means of translation method

Abstract: The translation method which can produce all the geometrical figures and closed phase equilibria diagram for multicomponent water-salt systems was described. The phase equilibria in quinaryNaCl - KCl -MgCl2 - CaCl2 - H2O (25°C) system which is an important part of the more complex oceanic Na, K, Mg, Ca//Cl, SO4- H2O system were determined using translation method. Three invariant points of quadruple saturation, tenmonovariant curves of triple saturation and twelvedivariant fields of double saturation salts wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 4 publications
0
10
0
2
Order By: Relevance
“…Transformed geometric images have formed correspond-ing phase diagram components on the n+1 level, according to their topological properties (fields, curved, points), taking into account the Gibbs phase rule for the n+1 component system. More detailed description of the translation method that can be used for predicting and constructing of equilibrium phase diagrams for the multicomponent water -salt systems are considered in the works [3][4][5]. Previously, this method was used to study the fivecomponent system [6].…”
Section: Resultsmentioning
confidence: 99%
“…Transformed geometric images have formed correspond-ing phase diagram components on the n+1 level, according to their topological properties (fields, curved, points), taking into account the Gibbs phase rule for the n+1 component system. More detailed description of the translation method that can be used for predicting and constructing of equilibrium phase diagrams for the multicomponent water -salt systems are considered in the works [3][4][5]. Previously, this method was used to study the fivecomponent system [6].…”
Section: Resultsmentioning
confidence: 99%
“…We have deduced phase equilibria in the Na,Ca||SO 4 ,CO 3 ,HCO 3 -H 2 O system at 100 °C using translation methods [4,5] which follows from the principle of compatibility of structural elements of n and n + 1 component systems in one diagram [6,7]. According to the translation method, the addition of one more component to the n-component system and its transition to the n + 1 component state is accompanied by transformation of the geometric image of the n-component system.…”
Section: Methodsmentioning
confidence: 99%
“…The transformed geometric images are translated to the n + 1 level according to their topological property in accordance with the Gibbs phase rule, forming correspondent geometric images (fields, curves, points) in the n + 1 component system. The application of translation methods for predicting and constructing phase diagram for multicomponent water-salt systems was considered in more details in our previous work [4]. Earlier this method was successfully used for other multicomponent systems [8,9].…”
Section: Methodsmentioning
confidence: 99%
“…It has been observed that the structures of Janecke diagrams of multicomponent water-salt systems can be obtained by means of translation method, which is more comprehensively described in literature (Soliev 1987(Soliev , 2000. For instance, the part saturated with sylvite forms a crystallization volume of sylvite that can be extracted from the phase equilibria diagram constructed by means of the translation method.…”
Section: Introductionmentioning
confidence: 99%